Islamic Education Values in Gayo Saman Dance - Shaumiwaty, Shaumiwaty; Yoga, Dharmika (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
Saman dance is a folk dance developed in the Gayo tribal community that inhabits several districts in Aceh Province. The origins of the dance are in harmony with the entry of Islam in Aceh and become a propaganda media in the spread of Islam. Then developed into an art that has a socio-cultural function and is the result of Islamic cultural acculturation. This study intends to examine the values of Islamic education contained in the symbols, the meaning of the movements and poetry of the Saman dance through ethnopedagogical analysis. The method used in this research is descriptive-qualitative method. The data source in this study consisted of primary data sources and secondary data sources, primary data sources were obtained from saman jalu dance video files and secondary data sources were obtained from interviews, books, video, and literatures. The results of the Saman dance research are known to be some of the values of Islamic education, namely, deliberation, courtesy to start guests, establish silaturrahmi, worship prayers, unity, obedience to leaders and scholars, love the motherland and habituation. This value is part of religious and moral education which has an important role in shaping the character of the Gayo tribe community.